Development of Cu(ii)-specific peptide shuttles capable of preventing Cu–amyloid beta toxicity and importing bioavailable Cu into cells. Issue 40 (30th September 2022) - Okafor, Michael; Gonzalez, Paulina; Ronot, Pascale; El Masoudi, Islah; Boos, Anne; Ory, Stéphane; Chasserot-Golaz, Sylvette; Gasman, Stéphane; Raibaut, Laurent; Hureau, Christelle; Vitale, Nicolas; Faller, Peter
Abstract : The synthetic peptide AKH-αR5W4 NBD was designed as a shuttle to counteract copper imbalance in Alzheimer's disease. In vitro, this shuttle is able to abstract Cu(ii ) selectively from amyloid-β and transport it into cells in a bioavailable form. Abstract : Copper (Cu) in its ionic forms is an essential element for mammals and its homeostasis is tightly controlled. Accordingly, Cu-dyshomeostasis can be lethal as is the case in the well-established genetic Wilson's and Menkes diseases. In Alzheimer's disease (AD), Cu-accumulation occurs in amyloid plaques, where it is bound to the amyloid-beta peptide (Aβ). In vitro, Cu–Aβ is competent to catalyze the production of reactive oxygen species (ROS) in the presence of ascorbate under aerobic conditions, and hence Cu–Aβ is believed to contribute to the oxidative stress in AD. Several molecules that can recover extracellular Cu from Aβ and transport it back into cells with beneficial effects in cell culture and transgenic AD models were identified. However, all the Cu-shuttles currently available are not satisfactory due to various potential limitations including ion selectivity and toxicity. Hence, we designed a novel peptide-based Cu shuttle with the following properties: (i) it contains a Cu(ii )-binding motif that is very selective to Cu(ii ) over all other essential metal ions; (ii) it is tagged with a fluorophore sensitive to Cu(ii )-binding and release; (iii) it is made of a peptide platform, which is very versatile to add new functions. The work presented here reports on the characterization of AKH-αR5W4 NBD, which is able to transport Cu ions selectively into PC12 cells and the imported Cu appeared bioavailable, likely via reductive release induced by glutathione. Moreover, AKH-αR5W4 NBD was able to withdraw Cu from the Aβ1–16 peptide and consequently inhibited the Cu-Aβ based reactive oxygen species production and related cell toxicity. Hence, AKH-αR5W4 NBD could be a valuable new tool for Cu-transport into cells and suitable for mechanistic studies in cell culture, with potential applications in restoring Cu-homeostasis in Cu-related diseases such as AD.